MYCN as an oncogene in pediatric brain tumors - Adriana Fernandez Garcia; Adriana Fernandez Garcia; Jayden Jackson; Jayden Jackson; Poorvi Iyer; Poorvi Iyer; Elissa G. Oliver; Elissa G. Oliver; Kosuke Funato; Kosuke Funato (Frontiers in Oncology)
MYCN, or N-Myc, is a member of the MYC family of transcription factors, which plays a key role in tumor formation by regulating genes involved in proliferation, differentiation, and apoptosis. MYCN is essential for neural development, especially for the appropriate growth and differentiation of neural progenitor cells, and its aberrant expression contributes to tumorigenesis. Gene amplification and mutations of this gene have been observed in a wide variety of cancer types, particularly in pediatric brain and non-brain tumors, such as neuroblastoma. Previous studies have provided extensive insights into the complex regulatory network of this transcription factor. Additionally, the presence of MYCN alterations in patient tumors serve as a key factor for risk stratification, as it correlates with poorer outcomes, and presents a significant challenge for treatment. Despite its clinical significance, therapeutic targeting of MYCN is challenging due to its structure, nuclear localization, and complex regulatory pathways. Efforts to target MYCN have focused on destabilizing the protein, modulating epigenetic mechanisms, and disrupting its transcriptional network. This review explores the role of MYCN in different subtypes of pediatric brain tumors and highlights novel ongoing therapeutic approaches. However, further research is necessary to develop more effective therapies and improve survival outcomes for patients with MYCN-driven tumor.